2016
DOI: 10.1007/s00294-016-0653-8
|View full text |Cite
|
Sign up to set email alerts
|

Telomere recombination pathways: tales of several unhappy marriages

Abstract: All happy families are alike; each unhappy family is unhappy in its own way. --Leo Tolstoy, Anna Karenina

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 71 publications
0
16
0
Order By: Relevance
“…In addition, the invariably telomeric location of the active VSG would facilitate the DNA rearrangements mediating VSG switching. DNA recombination reactions at telomeres mediate the generation of sequence diversity within polymorphic gene families involved in phenotypic or antigenic variation which are frequently telomeric (Keely et al ., ; Scherf et al ., ; de Las Penas et al ., ; Lue and Yu, ). In T. brucei this is also the case, and the telomeric VSG can be switched either through telomere exchange or through gene conversions (Li, ; McCulloch et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the invariably telomeric location of the active VSG would facilitate the DNA rearrangements mediating VSG switching. DNA recombination reactions at telomeres mediate the generation of sequence diversity within polymorphic gene families involved in phenotypic or antigenic variation which are frequently telomeric (Keely et al ., ; Scherf et al ., ; de Las Penas et al ., ; Lue and Yu, ). In T. brucei this is also the case, and the telomeric VSG can be switched either through telomere exchange or through gene conversions (Li, ; McCulloch et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Sir-mediated chromatin structure could also participate to telomere capping and limit resection at the terminal TG repeats protecting telomere from unwanted recombination events (Lue and Yu 2017).…”
Section: Limiting Resection In Heterochromatin: What Functional Consementioning
confidence: 99%
“…We termed them non-terminal arrests and showed that they were, at least partially, Mec1-and Pol32-dependent. Combined with evidence that recombination factors such as Rad51 and Rad52 are important for cell growth not only as an alternative telomere maintenance mechanism but even early after telomerase inactivation (Lundblad and Blackburn 1993;Le et al 1999;Khadaroo et al 2009;Churikov et al 2014;Fallet et al 2014;Xu et al 2015;Claussin and Chang 2016;Lue and Yu 2017), this result suggests that telomerase-negative cells frequently experience telomere-related damage, activate the DNA damage checkpoint and undergo repair events such as break-induced replication (BIR).…”
Section: Adaptation In Telomere-induced Replicative Senescencementioning
confidence: 99%